Legal Certainty of Reporting Granted Assets Without Authentic Deeds in the State Officials' Wealth Report System: Kepastian Hukum Pelaporan Harta Hibah Tanpa Akta Otentik Dalam Sistem Laporan Harta Kekayaan Penyelenggara Negara - Ananda Surya Dharma; Mella Ismelina Farma Rahayu (Universitas Muhammadiyah Sidoarjo, 2025)
Background General: Asset disclosure through the LHKPN system serves as a transparency mechanism to prevent corruption among state officials. Background Specific: In practice, several officials report granted assets without authentic deeds, even though Indonesian civil law requires notarial or PPAT deeds for the legal validity of grants. Knowledge Gap: No comprehensive study has specifically examined the legal certainty of reporting grants without authentic deeds in the LHKPN system or its interaction with civil law and anti-corruption regulations. Aims: This study analyzes the legal status of grants made without authentic deeds under Indonesian law and evaluates the legal certainty of their reporting within the LHKPN. Results: Findings indicate that grants lacking authentic deeds do not fulfill the formal requirements of Articles 1666, 1682, and 1868 of the Civil Code, rendering them invalid and lacking evidentiary strength. Their inclusion in the LHKPN creates legal uncertainty regarding ownership legitimacy and the accuracy of verification by the Corruption Eradication Commission. Novelty: The study provides an integrated analysis connecting civil law, administrative anti-corruption mechanisms, and legal certainty theory to the issue of non-authentic grant reporting. Implications: Normative clarification and regulatory harmonization are required to ensure that grants reported in the LHKPN possess lawful foundations, strengthening transparency, accountability, and the integrity of state officials. Highlights: Highlights the legal invalidity of grants without authentic deeds. Emphasizes the resulting uncertainty in LHKPN asset verification. Calls for regulatory harmonization to ensure accountable reporting. Keywords: Grant, Authentic Deed, Legal Certainty, LHKPN , Asset Reporting